COMPARISON OF SOIL RESPIRATION METHODS IN A MID-LATITUDE DECIDUOUS FOREST - Wayson C.A.; Randolph J.C.; Hanson P.J.; Grimmond C.S.B.; Schmid H.P. (My University, 2006)
In forest ecosystems the single largest respiratory flux influencing net ecosystem productivity (NEP) is the total soil CO2 efflux; however, it is difficult to make measurements of this flux that are accurate at the ecosystem scale. We examined patterns of soil CO2 efflux using five different methods: auto-chambers, portable gas analyzers, eddy covariance along and two models parameterized with the observed data. The relation between soil temperature and soil moisture with soil CO2 effluxes are also investigated, both inter-annually and seasonally, using these observations/results. Soil respiration rates (R soil) are greatest during the growing season when soil temperatures are between 15 and 25 °C, but some soil CO2 efflux occurs throughout the year. Measured soil respiration was sensitive to soil temperature, particularly during the spring and fall. All measurement methods produced similar annual estimates. Depending on the time of the year, the eddy covariance (flux tower) estimate for ecosystem respiration is similar to or slightly lower than estimates of annual soil CO2 efflux from the other methods. As the eddy covariance estimate includes foliar and stem respiration which the other methods do not; it was expected to be larger (perhaps 15–30%). The auto-chamber system continuously measuring soil CO2 efflux rates provides a level of temporal resolution that permits investigation of short- to longer term influences of factors on these efflux rates. The expense of building and maintaining an auto chamber system may not be necessary for those researchers interested in estimating R soil annually, but auto-chambers do allow the capture of data from all seasons needed for model parameterization.
Keywords: CARBON CYCLING; CO2 EFFLUX; DECIDUOUS FORESTS; NET ECOSYSTEM PRODUCTIVITY; SOIL RESPIRATION